Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1099/mic.0.28455-0
|View full text |Cite
|
Sign up to set email alerts
|

The Sinorhizobium meliloti chromosomal origin of replication

Abstract: The predicted chromosomal origin of replication (oriC) from the alfalfa symbiont Sinorhizobium meliloti is shown to allow autonomous replication of a normally non-replicating plasmid within S. meliloti cells. This is the first chromosomal replication origin to be experimentally localized in the Rhizobiaceae and its location, adjacent to hemE, is the same as for oriC in Caulobacter crescentus, the only experimentally characterized alphaproteobacterial oriC. Using an electrophoretic mobility shift assay and puri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 53 publications
3
31
0
Order By: Relevance
“…5 A and B) (21). A previously verified DnaA-binding motif upstream of the repABC operon of pSymA was identified by this analysis, as well as a conserved CtrAbinding motif 90 bp downstream of the DnaA site (11). The presence of these binding motifs suggests a possible interplay between CtrA and DnaA in the regulation of expression of this repABC operon on pSymA during the cell cycle.…”
Section: Microarray Analysis Of Synchronized S Meliloti Cultures Idementioning
confidence: 87%
See 2 more Smart Citations
“…5 A and B) (21). A previously verified DnaA-binding motif upstream of the repABC operon of pSymA was identified by this analysis, as well as a conserved CtrAbinding motif 90 bp downstream of the DnaA site (11). The presence of these binding motifs suggests a possible interplay between CtrA and DnaA in the regulation of expression of this repABC operon on pSymA during the cell cycle.…”
Section: Microarray Analysis Of Synchronized S Meliloti Cultures Idementioning
confidence: 87%
“…The results of this study suggest that the S. meliloti cell cycle transcriptional regulatory network, especially the regulon of the master regulator CtrA, has adapted specifically to fit its lifestyle both within the soil and its legume host. are essential and/or functionally conserved in S. meliloti, our understanding of the role of transcriptional regulation in the S. meliloti cell cycle and the link between the cell cycle and cellular differentiation during symbiosis has been limited (11,12,24,25).…”
Section: Significancementioning
confidence: 99%
See 1 more Smart Citation
“…This phenotype is correlated with blocked cell division (Latch & Margolin, 1997;Wright et al, 1997;Sibley et al, 2006) and loss of normal control of DNA replication initiation (Wright et al, 1997). It remains to be established whether a blockage in cell division always leads to branching in S. meliloti; however, this possibility is of considerable interest given the cellular morphology of N 2 -fixing bacteroids.…”
Section: Discussionmentioning
confidence: 99%
“…Examples include those overexpressing ccrM (78), ftsZ (41), dnaA (65), and min genes (7) or undergoing treatment with DNA-damaging agents (41). Begg and Donachie (2a) have indicated that when cell division is blocked, cells continue to increase in mass by elongating into filaments many times the length of the dividing cells.…”
Section: Resultsmentioning
confidence: 99%